Analisis Peran Badan Pengawas Pemilu Kabupaten Boyolali Dalam Kasus Pelanggaran Netralitas Kepala Desa Pada Pemilu Tahun 2024 - Murtini , Intan Yuli; Tara, Angela; Puspaningrum, Puspaningrum (Indonesian Journal Publisher, 2025)
The General Election (Pemilu) is an important element in the democratic system that requires the neutrality of village heads to ensure the continuation of free and fair elections. This study aims to analyze the role of the Election Supervisory Agency (Bawaslu) of Boyolali Regency in overseeing and addressing violations of the neutrality of village heads in the 2024 Election. The approach used is normative legal research, which analyzes related regulations and the authority of Bawaslu in carrying out its supervisory duties. The research findings indicate that Bawaslu of Boyolali Regency plays a crucial role in overseeing village heads but faces various obstacles. The difficulty of gathering evidence, limited human resources, and political pressure at the local level are the main challenges in the supervision and enforcement process. In addition, the weak sanctions imposed on village heads who violate neutrality further undermine the effectiveness of supervision. This study recommends improved coordination between Bawaslu and relevant agencies, as well as the use of technology to strengthen oversight. More intensive socialization of the neutrality rules for village heads is also necessary to increase awareness and compliance with the applicable regulations. It is hoped that with these measures, the supervision of village head neutrality can be more effective, ensuring that the 2024 Election can take place transparently and democratically.